FRI0106 Preliminary results from a controlled trial (VISARA) to evaluate the humoural immune response to vaccines in RA patients treated with tocilizumab (TCZ). (23rd January 2014) - Bingham, C.O.; Rizzo, W.; Klearman, M.; Hassanali, A.; Upmanyu, R.; Kivitz, A.
Abstract : Background: TCZ is an IL-6-receptor signalling inhibitor licensed for use in RA. Because TCZ may impact how IL-6 affects T-cell activation and B-cell differentiation, response of TCZ-treated pts to vaccination is of interest. Data from small studies suggest TCZ does not negatively affect response to vaccination; more data are needed. Objectives: To evaluate effects of TCZ on response to 23-valent pneumococcal polysaccharide vaccine (23VPPV) and tetanus toxoid vaccine (TTV) in RA pts on MTX. Methods: This is a preliminary analysis from VISARA, an ongoing, controlled, open-label study in RA pts who have inadequate response/intolerance to ≥1 anti-TNF agent. Pts were stratified by age and randomised (2:1) to TCZ 8 mg/kg IV every 4 wks + MTX (Active) or MTX only (Control) for 20 wks. Baseline (BL) serology samples were collected 3 wks after the first infusion, just before vaccination with 23VPPV and TTV. At 8 wks, anti-pneumococcal and anti-tetanus antibody titres were evaluated. Endpoints were proportion of pts with positive response (2-fold or >1 mg/L increase in serum antibody titres) to ≥6 of 12 23VPPV serotypes (Primary) and proportion with positive response (4-fold or ≥0.2 mg/L increase in serum antibody titres) to TTV (Secondary) at 5 wks post-vaccination. Results: For this preliminary analysis, data are available for the first 74/91 enrolled pts and presented only for 61 pts who met the per-protocol criteria (i.e. received ≥1 dose of study medication and both vaccines, had available BL and 8-wk titre samples; no protocol violations). A numerically greater percentage of Control than Active pts responded to ≥6 of 12 23VPPV serotypes at wk 8 (65.0% [95% CI, 44.1-85.9%] vs 53.7% [95% CI, 38.4-68.9%]). Greater proportion of Control than Active pts responded to serotype combinations (from ≥1 to ≥12). However, there was a notable degree of variability between pts as reflected by wide CIs within both groups, particularly for the higher number of serotype combinations (graph). The percentage of responders to TTV was comparable between groups (Active [43.9%; 95% CI, 28.7-59.1%] vs Control [36.8%; 95% CI, 15.2-58.5%]). Conclusions: Results suggest TCZ- and MTX-treated RA pts have comparable recall response to TTV, but response to 23VPPV is slightly reduced with TCZ. If possible, pneumococcal polysaccharide vaccination should be given before initiating TCZ to maximise response. These data are for 2 TCZ infusions and may only reflect initial effects of TCZ on the humoural immune response. Effects of long-term dosing are not addressed. Disclosure of Interest: C. Bingham III Grant/Research support from: Roche/Genentech, Consultant for: Roche/Genentech, W. Rizzo Grant/Research support from: Advanced Arthritis Care and Research, Consultant for: UCB, Savient, Speakers Bureau: Amgen, Takeda, UCB, Roche, Abbott, M. Klearman Employee of: Roche/Genentech, A. Hassanali Employee of: Roche/Genentech, R. Upmanyu Employee of: Roche, A. Kivitz Speakers Bureau: Roche